2004
DOI: 10.1086/383562
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Hydrogen in the Ionized Region of Planetary Nebulae

Abstract: This paper presents an analysis of the concentration of the hydrogen molecule inside the ionized region of planetary nebulae. The equations corresponding to the ionization and chemical equilibria of H, H+, H-, H2, H2+, and H3+ are coupled with the equations of ionization and thermal balance for a photoionized atomic gas. Forty different reactions related to the formation or the destruction of these species are included. The presence of dust is taken into account, since grains act as catalysts for the productio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 71 publications
2
50
0
Order By: Relevance
“…An independent study by Guerrero et al (2000) found definite H 2 detections in 13/15 bipolar PNe. These encouraging results are supported theoretically by Aleman & Gruenwald (2004) who modelled the physical conditions responsible for the presence of H 2 in PNe. They found higher H 2 mass fractions are associated with higher central star temperatures, which is consistent with the higher than average temperatures amongst bipolar PNe (Corradi & Schwarz 1995), thereby providing a simple physical explanation of Gatley's rule.…”
Section: Gatley's Rule and Mid-infrared Imagingsupporting
confidence: 55%
“…An independent study by Guerrero et al (2000) found definite H 2 detections in 13/15 bipolar PNe. These encouraging results are supported theoretically by Aleman & Gruenwald (2004) who modelled the physical conditions responsible for the presence of H 2 in PNe. They found higher H 2 mass fractions are associated with higher central star temperatures, which is consistent with the higher than average temperatures amongst bipolar PNe (Corradi & Schwarz 1995), thereby providing a simple physical explanation of Gatley's rule.…”
Section: Gatley's Rule and Mid-infrared Imagingsupporting
confidence: 55%
“…H À + h followed by the H + H À ! H 2 + e À mechanism (see Aleman & Gruenwald 2004;Natta & Hollenbach 1998). We note that our total column density for the neutral carbon, N C i; tot ¼ 2:2 ; 10 14 cm À2 , is $2 orders of magnitude higher than what is expected for N C i; tot in typical H ii regions, as discussed in Appendix A of Jenkins & Shaya (1979).…”
Section: I Fine-structure Pressure Diagnosticmentioning
confidence: 57%
“…The transition from fully ionized gas to neutral gas will be gradual and the transition layer will have a considerable thickness. Aleman & Gruenwald (2004) stopped their calculations when n(H + )/n H = 10 −4 was reached 1 . Cloudy by default stops when the electron temperature drops below 4000 K, based on the notion that at lower temperatures the forbidden optical emission lines will no longer be excited effectively and the stopping radius will coincide with the outer radius in optical images of the nebula.…”
Section: Can H 2 Survive In the Ionized Region?mentioning
confidence: 99%